Feasibility, Patient Acceptability, and Preliminary Efficacy of a Culturally Informed, Health Promotion Program to Improve Glaucoma Medication Adherence Among African Americans: "Glaucoma Management Optimism for African Americans Living with Glaucoma" (GOAL). (2nd January 2016) - Dreer, Laura E.; Owsley, Cynthia; Campbell, Lisa; Gao, Liyan; Wood, Andy; Girkin, Christopher A.
Abstract: Purpose/Aims : To examine the feasibility, patient acceptability, and preliminary effectiveness of a culturally informed, health promotion program designed to improve glaucoma medication adherence among African American's (AA's) with glaucoma. Materials/Methods : A sample of 11 AA glaucoma patients (mean age 61 years; 73% women and 27% men) completed a culturally informed and individually tailored, health promotion program developed for AAs titled, " G laucoma Management O ptimism for A frican Americans L iving with Glaucoma" (GOAL )©. The aim of the brief 4-week program is to enhance glaucoma medication adherence through a combination of education, motivational interviewing (MI), and problem-solving training (PST). Feasibility was assessed on the basis of patient satisfaction with the program, number of sessions completed, and length of sessions. Preliminary efficacy was evaluated using a pre-post design to determine whether the program improved objective glaucoma medication adherence via an electronic Travalert dosing aid as well as satisfaction with aspects of glaucoma treatment, health beliefs about medications, glaucoma symptoms, emotional well-being, and intraocular pressure. Results : Overall patient satisfaction and acceptability was high for the program, interactions with the health educator, program materials, and the length of sessions. Feasibility was also supported given the need for the program, success in recruitment/retention, and ease of implementing the program with AA glaucoma patients in clinic and/or over the telephone. In terms of preliminary efficacy, patients showed significant pre-post improvements in objective medication adherence rates by 15% ( p = 0.03), self-efficacy for glaucoma management ( p = 0.02), ease of use in administering eye drops ( p = 0.03), glaucoma treatment satisfaction ( p = 0.05), beliefs about the necessity of taking glaucoma medications ( p = 0.05), and functional visual ocular symptoms ( p = 0.03). Conclusions : (GOAL )© holds great promise toward improving glaucoma medication adherence and beliefs among AA's with glaucoma.